Modified N-acyl-L-homoserine lactone compounds abrogate Las-dependent quorum-sensing response in human pathogen Pseudomonas aeruginosa - Ballante, Flavio; Turkina, Maria V.; Ntzouni, Maria; Magnusson, Karl-Eric; Vikström, Elena (Frontiers in Molecular Biosciences, 2023)
Quorum sensing (QS) is a mode of cell-cell communication that bacteria use to sense population density and orchestrate collective behaviors. The common opportunistic human pathogen Pseudomonas aeruginosa employs QS to regulate a large set of genes involved in virulence and host-pathogen interactions. The Las circuit positioned on the top of the QS hierarchy in P. aeruginosa, makes use of N-acyl-L-homoserine lactones (AHL) as signal molecules, like N-3-oxo-dodecanoyl-L-homoserine lactone (3O-C12-HSL). Disabling QS circuits by certain small-molecule compounds, known as quorum-sensing inhibitors (QSI), has been proposed as a strategy to attenuate bacterial pathogenicity. In this study, four new AHL analogues were designed by incorporating a tert-butoxycarbonyl Boc group in amide and β-keto (3-oxo) moiety and evaluated on a molecular and phenotypic basis as QSI using screening strategy linked to the assignment of the Las QS system in P. aeruginosa. Using a LasR-based bioreporter, we found that the compounds decreased LasR-controlled light activity and competed efficiently with natural 3O-C12-HSL. The compounds reduced the production of the cognate 3O-C12-HSL and certain virulence traits, like total protease activity, elastase activity, pyocyanin production and extracellular DNA release. Further, a quantitative proteomic approach was used to study the effect of the compounds on QS-regulated extracellular proteins. Indeed, among four compounds tested, one of them resulted in a most significant difference in appearance of the 3O-C12-HSL-responsive reference proteins related to QS communication and virulence, i.e., a distinct activity as QSI. Moreover, by combining experimental data with computational chemistry, we addressed the effect of LasR protein flexibility on docking precision and assessed the advantage of using a multi-conformational docking procedure for binding-mode prediction of LasR modulators. Thus, the four new AHL compounds were tested for their interaction with the AHL binding site in LasR to identify the key interferences with the activity of LasR. Our study provides further insight into molecular features being required for small molecule modulation of LasR-dependent QS communication in P. aeruginosa. This should provide a valuable step in a rational design of the next generation of antivirulence tools to study and manipulate QS-controlled fitness in bacteria, and thereby a new way to handle bacterial infections.